Vile Incubator: A Pathology of the Cold War Bunker. - Flintham, Matthew (Journal of War & Culture Studies, 2020)
This article presents a 'pathology' of the Cold War bunker via an analysis of the decay, entropy and post-human fecundity to be found within the closed system of these now abandoned man-made protective cavities. Opening with a contextual overview of current research in bunker studies, and providing an orientation to the variety of bunkers to be found across the US, UK and Europe, the article then presents fieldwork in recently opened bunker caves on the Norwegian island of Tjøme, foregrounding the complex's after-life as an incubator for the extremophilic organisms and crystalline formations growing within it. These inhabitants adapt the bunker, producing a post-human 'bunker culture' of sorts, manifested in alien forms of survival and inter-organism conflict, that strangely echo Cold War science's research into entropy and cybernetics, and that war's co-option of matter and culture to apocalyptic, existential ends.